Oral Health in the Population Assessment of Tobacco and Health Study. (August 2022) - Chaffee, B.W.; Lauten, K.; Sharma, E.; Everard, C.D.; Duffy, K.; Park-Lee, E.; Taylor, E.; Tolliver, E.; Watkins-Bryant, T.; Iafolla, T.; Compton, W.M.; Kimmel, H.L.; et al.
Tobacco use is a well-established risk factor for multiple adverse oral conditions. Few nationally representative oral health data sets encompass the current diversity of tobacco and nicotine products. This investigation examines the validity of oral health measures in the Population Assessment of Tobacco and Health (PATH) Study to assess relationships between tobacco use and oral health. Cross-sectional data from PATH Study wave 4 ( N = 33, 643 US adults, collected 2016–2018) were used to obtain estimates for 6 self-reported oral conditions (e.g., bone loss around teeth, tooth extractions) and compared with analogous estimates from the National Health and Nutrition Examination Survey (NHANES) cycle 2017–2018 ( N = 5, 856). Within the PATH Study, associations were calculated between tobacco use status and lifetime and past 12-mo experience of adverse oral conditions using survey-weighted multivariable logistic regression. Nationally representative estimates of oral conditions between the PATH Study and NHANES were similar (e.g., ever-experience of bone loss around teeth: PATH Study 15.2%, 95% CI, 14.4%–15.9%; NHANES 16.6%, 95% CI, 14.9%–18.4%). In the PATH Study, combustible tobacco smoking was consistently associated with lifetime and past 12-mo experience of adverse oral health (e.g., exclusive cigarette smoking vs. never tobacco use, adjusted odds ratio [AOR] for loose teeth in past 12 mo: 2.02; 95% CI, 1.52–2.69). Exclusive smokeless tobacco use was associated with greater odds of loose teeth (AOR, 1.93; 95% CI, 1.15–3.26) and lifetime precancerous lesions (AOR, 3.85; 95% CI, 1.73–8.57). Use of other noncigarette products (e.g., pipes) was inconsistently associated with oral health outcomes. PATH Study oral health measures closely align with self-reported measures from NHANES and are internally concurrent. Observed associations with tobacco use and the ability to examine emerging tobacco products support application of PATH Study data in dental research, particularly to examine potential oral health effects of novel tobacco products and longitudinal changes in tobacco use behaviors.